Development of survey instruments for assessing walkability and bikeability for the prevention indicator system of the German federal states Entwicklung von Befragungsinstrumenten zur Erfassung von Walkability und Bikeability für das Präventionsindikatorensystem der Länder - Tristram, Clara; Finger, Jonas D.; John, Sophie; Manz, Kristin; Reimers, Anne Kerstin (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2025)
Background: Physical activity is an important behavioural determinant of health that can be influenced by designing a physical activity-friendly environment. The aim of this work was to develop survey instruments for walkability and bikeability for the prevention reporting of the federal states. Methods: As part of the project „Monitoring physical activity and promoting exercise - developing indicators for the federal states’ prevention indicator system in Germany (KAB-Mon)“ (01/05/2023–30/04/2026), the development and review of two instruments designed to subjectively assess the two prevention indicators walkability and bikeability were carried out in three steps. In Step 1, a systematic literature review was conducted. In Step 2, an expert survey followed in which 9 and 7 experts from 6 disciplines evaluated the items of both instruments using the specific criteria in an online survey. Step 3 involved cognitive testing through guided interviews with a total of 18 participants. The expert survey was analysed using mean comparisons, while the cognitive interviews were evaluated descriptively. Results: Based on the expert feedback, the walkability instrument was shortened from 16 to 13 items, and the bikeability instrument from 19 to 14 items. Following the cognitive testing, both instruments were supplemented with a fifth response option (“don’t know/no answer”). Discussion: The instruments developed through this project provide a solid scientific approach for the subjective assessment of walkability and bikeability in the German-speaking context.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Health promotion; Indicator development; Infrastructure quality; Mobility behavior; Urban planning